Pengembangan Inovasi Kemasan Produk UMKM Tarekli Khas Salama Kota Bima - Purnama, Ita; Putri, Nurkaidah; Safitri, Juhana (CV. Devi Tara Innovations, 2025)
The COVID-19 pandemic has driven many businesses to innovate, particularly in product branding and packaging to remain competitive in the digital era. This community service project aimed to empower local SMEs in Salama, Kota Bima, with a focus on the traditional snack